Det forudsigeliges uforudsigelighed - Qvortrup Fibiger, Marianne (Religionsvidenskabeligt tidsskrift, 2000)
The last decade has seen an increased interest in ethnography and anthropology among researchers of other fields who are studying culture in one way or another. At the same time ethnography and anthropology have realized the necessity of discussing their own theoretical and methological viewpoints. One of the main features in anthropological method is fieldwork. Here you participate, overtly or covertly, in people’s daily lives for an extended period of time, or on special occasions, watching what is going on, listening to what is being said, asking questions, and in this way collecting data that can throw light on the issues that you are concerned about.This article discusses fieldwork as a useful strategy in the study of religion with living representatives. It discusses the new possibilities that can be obtained by fieldwork, but also the mistakes that fieldwork can lead to if the researchers do not take into account several uncertain factors - some of which are being pointed out in the article. This means that a researcher engaged in fieldwork must be an engineer having a special methodological and theoretical intake to a specific study but, at the same time, she must take account of bricolage, being a bricoleur herself.By using some of Carlo Ginzberg's viewpoints, this article also discusses the differences and similarities in historical and anthropological method and ends up pleading for a methological pluralism when dealing with “living religion”.